Emergency management with ZigBee and GIS - Kawamura, Youhei; Veenendaal, B.; Dewan, A.; Hayashi, M.; Kitahara, I.; Nobuhara, H.; Ishii, K. (Kaoru Hirota, 2012)
Communications network damage resulting from a large disaster causes difficulties in the ability to rapidly understand the current situation and thus make appropriate decisions toward mitigating problems. This research focuses on the rapid construction of a network after a disaster occurs. This study suggests ZigBee and GIS technologies to resolve these problems and provide an effective communications system. This paper provides ground design of the emergency management system with ZigBee network and GIS technologies. In this paper, it was demonstrated the effectiveness of establishing such a communications system for supporting efforts to relieve disaster-damaged areas.